Solid state organic amine detection in a photochromic porous metal organic framework - Mallick, Arijit; Garai, Bikash; Addicoat, Matthew A.; Petkov, Petko St.; Heine, Thomas; Banerjee, Rahul (Chemical Science, 2015)
A new Mg(II) based photochromic porous metal-organic framework (MOF) has been synthesized bearing naphthalenediimide (NDI) chromophoric unit. This MOF (Mg-NDI) shows instant and reversible solvatochromic behavior in presence of solvents with different polarity. Mg-NDI also exhibits fast and reversible photochromism via radical formation. Due to the presence of electron deficient NDI moiety, this MOF exhibits selective organic amine (electron rich) sensing in solid state. The organic amine detection has been confirmed by photoluminescence quenching experiment and visual color change.